Food-Based Interventions to Modify Diet Quality and Diversity to Address Multiple Micronutrient Deficiency - Nair, Madhavan K.; Augustine, Little Flower; Konapur, Archana (Frontiers in Public Health, 2016)
Global data indicates a high prevalence of hidden hunger among population. Deficiencies of certain micronutrients such as folic acid, iodine, iron and vitamin A have long lasting effects on growth and development and therefore have been a National priority from many decades. The strategy implemented so far limits to the use of supplemental sources or fortified foods in alleviating the burden of deficiencies. These approaches however undermine the food based strategies involving dietary diversification as the long term sustainable strategy. There is lack of understanding on the level of evidence needed to implement such strategies and the level of monitoring required for impact evaluation. Dietary diversity concerns how to ensure access for each individual to a quality and safe diet with adequate macro and micronutrients. The key to success in using dietary diversity as a strategy to tackle hidden hunger is in integrating it with the principles of bioavailability, translated to efficient food synergies with due emphasis on food accessibility, affordability and outdoor physical activity/ life style modifications. Promoting enabling environment and sustainable agriculture is crucial for practicing dietary diversification with behaviour change communication as an integral segment. It can be concluded that food based strategies require careful understanding of the factors associated with it and moderate it to form an effective strategy for controlling multiple micronutrient deficiencies.